Remittances and Sustainable Development Goals: An Overview of Opportunities and Challenges in MENA Countries - Mabrouk, Fatma (Journal of Ecohumanism, 2024)
Migrations and remittances play a significant role in the development of different economies and have the potential to contribute to the achievement of the Sustainable Development Goals (SDGs). This article deeply reviews the relationship between migrations, particularly remittances and countries' progress toward the SDGs. Based on 122 articles extracted from the Web of Science database during the period 2003-2024, a bibliometric analysis, systematic review, and clustering exploration, the study aims to verify whether the scientific literature brings together sufficiently solid evidence to precisely answer the question of how significantly remittances contribute to the accomplishment of SDGs. Using VOSviewer, a rigorous, structured and reproducible software for information synthesis, the investigation examines the various connections between migrations and remittances, including economic, social, and environmental aspects, and highlights the challenges and opportunities associated with harnessing migrations and remittances for sustainable development in MENA countries. Findings encourage future scientific research to focus more on topics related to Remittances and SGDs 14, 17, 16, 7, 5 and 6. Through this comprehensive analysis, policymakers and stakeholders can gain valuable insights into the role of migrations and remittances in promoting SDGs. In addition, it helps researchers to point out any gaps or areas in the literature that require more investigation.